Illiquidity or credit deterioration: A study of liquidity in the US corporate bond market during financial crises - Friewald, Nils; Jankowitsch, Rainer; Subrahmanyam, Marti G. (Journal of Financial Economics, 2012)
We investigate whether liquidity is an important price factor in the US corporate bond market. In particular, we focus on whether liquidity effects are more pronounced in periods of financial crises, especially for bonds with high credit risk, using a unique data set covering more than 20,000 bonds, between October 2004 and December 2008. We employ a wide range of liquidity measures and find that liquidity effects account for approximately 14% of the explained market-wide corporate yield spread changes. We conclude that the economic impact of the liquidity measures is significantly larger in periods of crisis, and for speculative grade bonds.